Peran Kepemimpinan Transformasional dalam Membangun Budaya Organisasi yang Positif: Kajian Pustaka - Firdaus, Kharisma; Naurahanif, Rosilia; Abdullah, Muhamad Lendran Anu Swaran (Universitas Pahlawan Tuanku Tambusai, 2024)
This study investigates the role of transformational leadership in fostering a positive organizational culture. Characterized by inspiring, motivating, and empowering organizational members, transformational leadership is considered a key factor in creating productive and sustainable work environments. Through a literature review and case analysis, this research identifies relevant dimensions of transformational leadership, such as a clear vision, effective communication, emotional support, and intellectual stimulation. Findings indicate that transformational leaders play a pivotal role in shaping positive norms, values, and behaviors within organizations. Transformational leadership can cultivate a strong sense of belonging and engagement among employees, enhance organizational performance, and stimulate innovation. Additionally, this study discusses challenges and barriers to implementing transformational leadership and provides practical implications for leaders and organizations